Produção e caracterização de leptina e TcPTP1 recombinantes, proteínas ligadas ao metabolismo, sinalização celular e inflamação - Gallo, Gloria [UNIFESP] (2010)
Leptin is predominantly secreted by adipocytes and plays an important role in the regulation of the energetic metabolism of mammals. Because of this, leptin is strongly involved in the regulation of obesity. After ligation, dimerization and activation of its specific receptor in the hypothalamus, leptin activates JAK kinases that phosphorylate STAT transcription factors, which in turn up-regulate energetic expenditure and lead to the inhibition of hunger. Leptin signalling is downregulated by a phosphotyrosine phosphatase named PTP1B. The aim of this work is the cloning, expression and purification of recombinant human leptin in E. coli. After induction, recombinant leptin was produced in E.coli BL21(DE3) in an insoluble form, purified by nickel-afinity chromatography, refolded using serial dialysis and concentrated up to 3mg/ml. Injection of this recombinant protein in ob/ob mice, which are devoid of leptin, leads a reduction of body weight by 8% and a reduction of food intake by 50%, thus confirming the biological activity of the protein. In order to enrich this study, we produced a targeted mutation of this recombinant leptin (called mutein) wich act as an antagonist. In other hand, Additionaly to this work, we also cloned, expressed, purified and biochemically characterized a phosphotyrosine phosphatase from Trypanosoma cruzi termed TcPTP1, which is homologous to mammalian PTP1B. TcPTP1 is an interesting medical target because of its potential influence in the regulation of cell signalling in T.cruzi. The production and biochemical characterization of TcPTP1 is the basis for functional and structural studies that can lead to the design of new inhibitors of this enzyme, which seems to be vital for the parasite.